2021
DOI: 10.3390/ijerph18052272
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Psychological Skills Training for Archery Players in Korea: Research Synthesis Using Meta-Analysis

Abstract: The purpose of this meta-analysis study was to investigate the effectiveness of psychological skills training interventions for archery players in Korea. A total of 17 research papers examining the effects of psychological skills training interventions were selected for data analysis. To analyze the data, the Comprehensive Meta-Analysis (CMA) software program was used. The results of this study were as follows: The overall effect size of psychological skills training interventions for archery players was ES = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
9
0
2
Order By: Relevance
“…Archery characteristics have many components that can be increase of the students' self-confidence, so they are very enthusiastic because they get more material in a fun way. The results of this study are supported by previous studies which reported that archery learning effects on the development of self-confidence (Kim et al, 2021). In addition, the factor causing students confidence learn to increase is because of archery is a fun game, so it can reduce the level of fear, boring in participating learning activities (Aysan, 2016).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Archery characteristics have many components that can be increase of the students' self-confidence, so they are very enthusiastic because they get more material in a fun way. The results of this study are supported by previous studies which reported that archery learning effects on the development of self-confidence (Kim et al, 2021). In addition, the factor causing students confidence learn to increase is because of archery is a fun game, so it can reduce the level of fear, boring in participating learning activities (Aysan, 2016).…”
Section: Resultssupporting
confidence: 86%
“…This research finds that archery is an effective tool to increasing of both psychological aspects during the COVID-19 era. Many previous studies have found that archery has many benefits, such as it can be increasing the psychological aspects of concentration, anxiety, motivation, and can control a person's mental condition (Kim et al, 2021). The results of this study serve as an empirical basis for learning archery using a PVC plywood bow as a training method to increase psychological changes that have an impact on archery player performance (Lee & Kwag, 2018).…”
Section: Resultsmentioning
confidence: 77%
“…Finally, the duration of psychological skills training is also thought to be an essential factor in the effectiveness of the psychological training program (34). While six-week training did not affect the psychological skills of the athletes (35), in this study, a ten-week program was performed on the study groups for psychological skills training.…”
Section: Discussionmentioning
confidence: 89%
“…Archery therapy is a sport that requires intense concentration and focus to aim at the target accurately. 5 In archery, it is necessary to increase strength, arm, leg and finger muscles endurance, so that it affects the accuracy of archery. 6 Archery is a static sport with a steady sequence of movements throughout the shot.…”
Section: Dear Editormentioning
confidence: 99%